2018
DOI: 10.1186/s13017-018-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

2018 WSES/SIS-E consensus conference: recommendations for the management of skin and soft-tissue infections

Abstract: Skin and soft-tissue infections (SSTIs) encompass a variety of pathological conditions that involve the skin and underlying subcutaneous tissue, fascia, or muscle, ranging from simple superficial infections to severe necrotizing infections. SSTIs are a frequent clinical problem in surgical departments. In order to clarify key issues in the management of SSTIs, a task force of experts met in Bertinoro, Italy, on June 28, 2018, for a specialist multidisciplinary consensus conference under the auspices of the Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
311
1
35

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(351 citation statements)
references
References 162 publications
4
311
1
35
Order By: Relevance
“…However, those factors were outside the scope of this review. The goal of the initial surgical procedure for NSTIs is to gain control and prevent further (trans-fascial and hematogenous) spreading of the infection by complete debridement of all the infected and necrotic tissue [1,9]. Sarani et al suggested that each hour delay of surgical treatment can lead to a local spread of the infection as fast as an inch per hour and results in higher chances of systematic spread [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, those factors were outside the scope of this review. The goal of the initial surgical procedure for NSTIs is to gain control and prevent further (trans-fascial and hematogenous) spreading of the infection by complete debridement of all the infected and necrotic tissue [1,9]. Sarani et al suggested that each hour delay of surgical treatment can lead to a local spread of the infection as fast as an inch per hour and results in higher chances of systematic spread [24].…”
Section: Discussionmentioning
confidence: 99%
“…Early resection of necrotic and infected tissue results in a lower microbial load. As a result, the immune system combined with broad spectrum antibiotics has better odds at controlling the infection [1,27]. Thus, time is of the essence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linezolid is used for the treatment of complicated skin and soft tissue infections with methicillin-resistant Staphylococcus aureus [1][2][3] and for toxic shock syndrome [4], and has become an important treatment option in empirical antimicrobial therapy in intensive care medicine, e.g., recommended in German guidelines for septic shock with a risk of methicillin-resistant Staphylococcus aureus (MRSA) infection [5]. In addition, linezolid is a frequently used antibiotic for the treatment of vancomycin-resistant Enterococcus (VRE), which is increasingly triggering serious infections in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%